2020
DOI: 10.1101/2020.10.24.20218727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation and gene expression pattern of ACE2 and TMPRSS2 genes in saliva samples of patients with SARS-CoV-2 infection

Abstract: COVID-19 caused by SARS-CoV-2 became a pandemic affecting the health and economy of the world. Although it was known that this virus uses ACE2 protein along with TMPRSS2 to enter the host cell, the methylation pattern and gene expression of ACE2 and TMPRSS2 genes are not explored in saliva samples of patients infected with COVID-19. The study aimed to quantify promoter methylation of ACE2 and TMPRSS2 along with its mRNA expression in saliva samples of COVID-19 patients in order to understand the regulatory mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Despite being covered by our assay, neither ACE2 nor TMPRSS2 genes, identified in the literature as key players for COVID-19 infection, showed differentially methylated regions in their proximity if comparing cases vs. controls. The same conclusion was reached in a study by Misra et al, despite a different tissue being interrogated [31].…”
Section: Discussionsupporting
confidence: 75%
“…Despite being covered by our assay, neither ACE2 nor TMPRSS2 genes, identified in the literature as key players for COVID-19 infection, showed differentially methylated regions in their proximity if comparing cases vs. controls. The same conclusion was reached in a study by Misra et al, despite a different tissue being interrogated [31].…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, a new study quantified promoter DNA methylation of ACE2 and TMPRSS2 genes compared to mRNA expression in saliva samples of COVID‐19 patients. 72 They revealed that DNA methylation of ACE2 has a significant positive relation with mRNA expression of ACE2 in COVID‐19 patients. Interestingly, recent studies highlighted noticeable epigenetic activities in the pathophysiology and severity processes of SARS‐CoV‐2 infections upon the regulation of ACE2 expression.…”
Section: Promising Applications For Exos Derived From Immune Cellsmentioning
confidence: 99%
“…As presented in Figure 4, it is possible that enriching MSC‐derived Exos with the EZH2 promoter could efficiently contribute to inducing chromatin remodelling and lowering ACE2 expression, which could help to prevent SARS‐CoV‐2 entry and replication. Moreover, a new study quantified promoter DNA methylation of ACE2 and TMPRSS2 genes compared to mRNA expression in saliva samples of COVID‐19 patients 72 . They revealed that DNA methylation of ACE2 has a significant positive relation with mRNA expression of ACE2 in COVID‐19 patients.…”
Section: Promising Applications For Exos Derived From Immune Cellsmentioning
confidence: 99%